New Automatized Method of 3D Multiculture Viability Analysis Based on Confocal Imagery: Application to Islets and Mesenchymal Stem Cells Co-Encapsulation - Chabert, Clovis; Laporte, Camille; Fertin, Arnold; Tubbs, Emily; Cottet-Rousselle, Cécile; Rivera, Florence; Orhant-Prioux, Magali; Moisan, Anaick; Fontaine, Eric; Benhamou, Pierre-Yves; Lablanche, Sandrine (Frontiers in Endocrinology, 2018)
Co-encapsulation of pancreatic islets with mesenchymal stem cells in a three-dimensional biomaterial’s structure is a promising technique to improve transplantation efficacy and to decrease immunosuppressant therapy. Currently, evaluation of graft quality after co-encapsulation is only based on insulin secretion. Viability measurement in a 3D conformation structure involving two different cell types is complex, mainly performed manually, highly time consuming and examiner dependent. Standardization of encapsulated graft viability analysis before transplantation is a key point for the translation of the method from the bench side to clinical practice. In this study, we developed an automated analysis of islet viability based on confocal pictures processing of cells stained with three probes (Hoechst, propidium iodide, and PKH67). When compared with results obtained manually by different examiners, viability results show a high degree of similarity (under 3% of difference) and a tight correlation (r = 0.894; p < 0.001) between these two techniques. The automated technique offers the advantage of reducing the analysis time by 6 and avoids the examiner’s dependent variability factor. Thus, we developed a new efficient tool to standardize the analysis of islet viability in 3D structure involving several cell types, which is a key element for encapsulated graft analysis in clinical practice.